2016
DOI: 10.1208/s12248-016-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

GDF11 Treatment Attenuates the Recovery of Skeletal Muscle Function After Injury in Older Rats

Abstract: Loss of skeletal muscle mass and function results in loss of mobility for elderly patients. Novel therapies that can protect and/or restore muscle function during aging would have profound effects on the quality of life for this population. Growth differentiation factor 11 (GDF11) has been proposed as a "youthful" circulating factor that can restore cardiac, neural, and skeletal muscle functions in aging animals. However, conflicting data has been recently published that casts doubt on these assertions. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Recently the observation has revealed that GDF11 and myostatin both inhibit myoblast differentiation, GDF11 significantly inhibits muscle regeneration and decreased satellite cell expansion in mice [71] . GDF11 treatment has resulted in a significant increase in tissue fibrosis, accompanied by attenuated functional recovery in a complex rat model of skeletal muscle injury that mimics physiological injuries seen in human patients [72] . The considerable attention focused on the blockade of activin receptor signaling for the suppression of skeletal muscle loss by soluble receptors and monoclonal antibodies [73] , [74] , [75] .…”
Section: Possible Therapeutic Intervention Strategiesmentioning
confidence: 97%
“…Recently the observation has revealed that GDF11 and myostatin both inhibit myoblast differentiation, GDF11 significantly inhibits muscle regeneration and decreased satellite cell expansion in mice [71] . GDF11 treatment has resulted in a significant increase in tissue fibrosis, accompanied by attenuated functional recovery in a complex rat model of skeletal muscle injury that mimics physiological injuries seen in human patients [72] . The considerable attention focused on the blockade of activin receptor signaling for the suppression of skeletal muscle loss by soluble receptors and monoclonal antibodies [73] , [74] , [75] .…”
Section: Possible Therapeutic Intervention Strategiesmentioning
confidence: 97%
“…Growth differentiation factor-11 (GDF11) and myostatin (GDF8) are members of the TGFβ superfamily that bind the activin type II receptor to mediate downstream activation of Smad2/Smad3 complex (McPherron et al, 2009). Defective regeneration of damaged muscle during aging correlates with increased GDF11 expression (Egerman et al, 2015; Zhou et al, 2016). …”
Section: Exercise Promotes Muscle Homeostasis In Agingmentioning
confidence: 99%
“…Furthermore, the same group demonstrated that circulating GDF11 increased with age and inhibited skeletal muscle regeneration . Correspondingly, recent studies indicated that GDF11 had no beneficial effect on skeletal muscle regeneration and function in dystrophic mice or on aging‐related pathologic hypertrophy; instead, rGDF11 injection attenuated the recovery of skeletal muscle function, worsened hepatocellular injury and liver regeneration, and induced cardiac and skeletal muscle dysfunction and wasting . Elevated GDF11 is even more of a risk factor for age‐related frailty and disease in humans .…”
Section: Introductionmentioning
confidence: 98%